ALT 40 African Literature Comes of Age - Emenyonu, Ernest N. (2023)
Explores and interrogates the many and diverse perspectives of the new frontiers of African literary studies. Publication of the seminal volume African Literature Comes of Age by C.D. Narasimhaiah (India) and Ernest N. Emenyonu (Nigeria), in 1988 generated the consciousness that African literature had attained maturity by the evolution of diverse concerns among scholars, critics, and researchers over the decades following the publication, in the English language, of Chinua Things Fall Apart in 1958. Since the publication of the first volume of African Literature Today in the 1970s, the writings of Africans across the continent have spread across the globe, constituting refreshing and hitherto unimaginable epistemologies. This 40th volume provides a serious critical response to those changing horizons and reflects African literature's maturity, diversity, scope, spread, and above all, relevance. The topics discussed range from sickle cell disease to the animalization of humans, new feminisms and stereotypes of womanhood, the different shades of black masculinity, and political exploitation in creative works. Reaching across boundaries, recent fictions are seen to suggest a widening of conventional literary genres, and new forms that change the known trajectories of dramatic theatre. The substance, freshness, and vitality that characterize the articles in this volume of African Literature Today bring a welcome perspective to the continent's rich creative life.